Pengaruh Model Project Science Based Learning Terhadap Keterampilan Berpikir Kritis dan Kreatif Siswa pada Topik Materi dan Perubahannya - Sa'diyah, Dwi Arini Nur Ilmiatus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
level with the topic of forms of matter and their changes. Based on the results of pre-research conducted through observations and interviews with science and natural sciences class IV A SD Tamansiswa Turen teachers, it was said that after students received the material concept regarding the shape of objects and their materials. changes, students are not yet fully able to identify the process by which substances form and the causes that result in changes in form. that substance. To make it easier for students to understand material about the forms of substances and their changes, a learning model is needed that can increase students' understanding. One learning model that can be used is the project based learning (PjBL) learning model. This is because the project based learning (PjBL) model can improve student skills, make students more active and creative, and can improve critical thinking skills when completing projects that have been designed and prepared individually or in groups. This research aims to determine whether or not there is an influence of the project-based learning model on students' critical and creative thinking abilities in class IV of the material changes at SD Tamansiswa Turen.The type of research used was quantitative research with a pre-experimental method of type one group pre-test and post-test design. This research was given to all students in grade IV A at SD Tamansiswa Turen which amounted to 22 students. The instruments used in this study are: 1) Processing instruments: Teaching Module, LKPD, Interview Guidelines, 2) Measurement instruments: written tests (pre-test and post-test) in the form of 10 essay questions for pre-test and 1 essay question for post-test. Data analysis used the liliefors analysis test for normality test while for hypothesis test used paired sample t-test. The results of the study showed that there was an influence of the project-based learning (PjBL) model on students' critical and creative thinking skills with an average pre-test score of 67,840 and an average post-test score of 80. It is known that the t-count value for critical and creative thinking skills is 5,430 with a probability (Sig.) of 0.001. So that the probability value is 0.05, then H0 is rejected and Ha is accepted. In addition, the results of the study also show the influence of PjBL on critical and creative thinking skills with the emergence of indicators of critical and creative thinking skills in the learning process. Thus, the project-based learning (PjBL) model can be used by teachers in schools for learning options or alternatives in improving students' critical and creative thinking skills.